Postindustrialna tożsamość śląskiego miasta na przykładzie Siemianowic Śląskich - Wądołowski, Marcin (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2017)
The article focuses on post-industrial identity of Silesian towns. The issue has been illustrated by the example of Siemianowice Śląskie. The author discusses the problem by showing the relations of the authorities with the industrial heritage of the town and by presenting the issue of Silesian character of the town, based on the result of sociological research. The paper creates an image of contemporary Silesian town which can be applied to other municipalities in Silesia.